Cytoplasmic DNAs: Sources, sensing, and roles in the development of lung inflammatory diseases and cancer - He, Xintong; Sun, Ye; Lu, Jianzhang; Naz, Faiza; Ma, Shenglin; Liu, Jian (Frontiers in Immunology, 2023)
Cytoplasmic DNA is emerging as a pivotal contributor to the pathogenesis of inflammatory diseases and cancer, such as COVID-19 and lung carcinoma. However, the complexity of various cytoplasmic DNA-related pathways and their crosstalk remains challenging to distinguish their specific roles in many distinct inflammatory diseases, especially for the underlying mechanisms. Here, we reviewed the latest findings on cytoplasmic DNA and its signaling pathways in inflammatory lung conditions and lung cancer progression. We found that sustained activation of cytoplasmic DNA sensing pathways contributes to the development of common lung diseases, which may result from external factors or mutations of key genes in the organism. We further discussed the interplays between cytoplasmic DNA and anti-inflammatory or anti-tumor effects for potential immunotherapy. In sum, this review aids in understanding the roles of cytoplasmic DNAs and exploring more therapeutic strategies.